(untitled) (Journal of Leadership, Accountability and Ethics, 2022)
Prior research has documented that diversity climate positively influences individual and organizational outcomes. However, there is void in current literature on how gender diversity influences subordinates’ perception of a leader’s effectiveness. In this paper, the researchers investigated how diversity climate affects the relationship between gender of leader and subordinate perceptions of a leader’s effectiveness. To investigate this problem, a convenience sampling method was used to select a gender-diverse faculty members sample at a research university in the southern region of the United States. The researchers analyzed the data using exploratory factor analysis to tease out significant factors that underlie structure of the diversity climate and perceptions of a leaders’ effectiveness scales. The data shows that diversity climate correlates with faculty’s gender and perceptions of leadership effectiveness. That finding also revealed that diversity climate does affect individual, unit, and/or organizational outcomes. The researchers recommended that additional studies be conducted to further examine diversity climate impact on leadership effectiveness and organizational outcomes as organizations embrace diversity, inclusion and equity.